Kinerja Lingkungan dan Pengungkapan Sustainability Reporting Terhadap Nilai Perusahaan dengan Moderasi Profitabilitas - Modjaningrat, Radina; bahri, syaiful (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The study aims to analyze the influence of environmental performance and sustainability reporting disclosure on firm value, with profitability as a moderating variable in consumer goods manufacturing companies listed on the Indonesia Stock Exchange. Firm value reflects investors' perceptions of a company's future performance and prospects, and is therefore influenced not only by financial performance but also by non-financial performance, particularly environmental and sustainability aspects. This study uses a quantitative approach with secondary data obtained from annual reports, sustainability reports, and official company publications. Environmental performance is measured using the PROPER rating, sustainability reporting disclosure is measured using the Global Reporting Initiative (GRI) index, firm value is measured using the Tobin's Q ratio, and profitability is measured by Return on Assets (ROA). The analytical methods used are multiple linear regression and moderated regression analysis (MRA). The results show that environmental performance and sustainability reporting disclosure have a positive effect on firm value. In addition, profitability is proven to strengthen the influence of environmental performance and sustainability reporting disclosure on firm value. These findings indicate that companies with good environmental performance and high levels of sustainability reporting disclosure, supported by strong profitability, tend to have higher firm value. This research provides implications that the implementation of sustainability practices is not only a form of compliance, but also a strategy to increase company value in a sustainable manner.